Removal of Eleven Live Puppies through Caesarean Section due to Complete Primary Uterine Inertia in a Saint Bernard Bitch - Kumar, Vinod; Sakshi,; Zingare, Saurabh; Kadam, Rahul G; Jena, Dayanidhi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine pregnancy, like other polytocous species, undergoes several challenges during gestation and  whelping due to multifactorial reasons like hormonal  changes, prolonged whelping process, nursing, and  subsequent uterine involution. Another factor which drives  canine pregnancy as a challenge is the presence of multiple  foetuses in utero which demands continuous yet consistent  contractile forces to expel them (Arlt et al., 2023). These  multiple foetuses predispose the dam to uterine inertia  which denotes the lack of contractile forces in the uterine  musculature. The primary uterine inertia is the inherent lack  of contractile forces and is referred as the cause of dystocia  whereas the secondary uterine inertia, which is due to  exhaustion and fatigue of uterus resulting in abnormal and  ineffective forces, is the result of dystocia. Between these  two the primary uterine inertia accounts 40-70% of maternal  factors related dystocia cases (Darvelid and Linde-Forsberg,  1994). The incidence of primary uterine inertia is high in  bitches and there are various factors which predispose this  condition like hormonal imbalance, age, litter size, genetic  predisposition etc (Davidson et al., 2011). Primary uterine  inertia is further subdivided into two classifications naming  partial and complete primary uterine inertia. The partial  one results after the initiation of normal labour followed by  delivery of one or few puppies but fail to deliver full litter  owing to abrupt cessation of myometrial contraction. On  the contrary, in the complete primary uterine inertia, the  second stage of whelping fails to occur resulting in dystocia  (Balamurugan et. al., 2024). This paper reports successful  removal of eleven live puppies post-exploratory laparotomy  due to complete primary uterine inertia in a bitch.
Keywords: Canine pregnancy; multifactorial